Retinoids Induce t-PA Synthesis by C6 Glioma Cells -Role in Tumoral Haemorrhagic Necrosis - Pernod, Gilles; Amalfltano, Guy; Le Magueresse, Brigitte; Berger, Francois; Polack, Benolt; Kolodie, Lucien (Thrombosis and Haemostasis, 1996)
Treatment of rat C6 glioma with high doses of 13 cis-retinoic acid (cRA) was responsible for death related to haemorrhagic necrosis localized to the tumor. Our aim was to explore this adverse effect of retinoid treatment. We show that cRA-treated C6 glioma at 25 mg/kg/day for 18 days exhibits in vivo an increased t-PA activity, which is responsible for a localized tumor fibrinolytic activity. Production of t-PA is supported by specific enhancement of gene expression, as was shown by the increase in t-PA mRNA (X 2.3). This production is a direct effect of cRA when treating the tumor, since tumor cells themself do not produce enough t-PA and treatment of control rats does not increase the t-PA level. t-PA production by rat C6 glioma is in vivo related to the specific synthesis of t-PA by the C6 cell-line. The stimulation of C6 cell-line by cRA in vitro is dose-dependent and reached a maximum for 3 and 30 |iM at the 72nd h. So cRA-treated C6 glioma cells produce t-PA which appears to be the major species associated with the fibrinolytic activity-induced intra-tumoral haemorrhage after exposure to retinoid treatment.